2012
DOI: 10.1107/s1600536812004412
|View full text |Cite
|
Sign up to set email alerts
|

Bis[4-amino-N-(pyrimidin-2-yl-κN)benzenesulfonamidato-κN](4,4′-dimethyl-2,2′-bipyridine-κ2N,N′)cadmium dimethylformamide disolvate

Abstract: In the title compound, [Cd(C10H9N4O2S)2(C12H12N2)]·2C3H7NO, the CdII ion lies on a twofold rotation axis, is six-coordinated by N atoms, and displays a trigonal–prismatic geometry arising from the two sulfadiazinate ligands and one 4,4′-dimethyl-2,2′-bipyridine ligand. Both ligands are bidentate and coordinate via their N atoms. The O and carbonyl C atoms of the dimethyl­formamide mol­ecule show disorder and were modelled with two different orientations and with site occupancies of 0.584 (10):0.416 (10). The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The bond angles around the S atom correspond to a distorted tetrahedral geometry. The bond distance C(18)-N(14) (Terminal amino group) of 1.371 (5) Å and the torsion angle C(15)-S(11)-N(11)-C(11) of 74.4 (4)° are larger than those observed in the related structures Hossain & Amoroso, 2012). The dihedral angle between the aromatic rings of the sulfamerazinate anion of 73.27 (13)° is larger than the value of 71.10 (14)° and smaller than the value of 76.60 (8)° (Hossain & Amoroso, 2012) in the sulfadiazinate anion.…”
Section: S1 Commentmentioning
confidence: 65%
“…The bond angles around the S atom correspond to a distorted tetrahedral geometry. The bond distance C(18)-N(14) (Terminal amino group) of 1.371 (5) Å and the torsion angle C(15)-S(11)-N(11)-C(11) of 74.4 (4)° are larger than those observed in the related structures Hossain & Amoroso, 2012). The dihedral angle between the aromatic rings of the sulfamerazinate anion of 73.27 (13)° is larger than the value of 71.10 (14)° and smaller than the value of 76.60 (8)° (Hossain & Amoroso, 2012) in the sulfadiazinate anion.…”
Section: S1 Commentmentioning
confidence: 65%
“…It has been shown that the activities of silversulfonamide complexes are superior to those of the sulfonamides alone or silver nitrate salts in most of the therapy cases (Baenziger & Struss, 1976;Miller et al, 2012). The crystal structures of metal-sulfadiazine with a coligand, such as 2,2 0bipyridine (Cabaleiro et al, 2000; Beloso et al, 2003; He et al, 2010), 4,4 0 -dimethyl-2,2 0 -bipyridine (Hossain & Amoroso, 2012), 1,10-phenanthroline (Hu et al, 2012), pyridine (Wang, Li et al, 2009;Wang, Zou et al, 2010), have also been reported, all of which were mononuclear. To contribute to the studies of metal-sulfadiazine complexes, we report here the synthesis and characterization of a cobalt(II) complex with sulfadiazine (HL) and 1,3-bis(pyridin-4-yl)propane (bpp), viz.…”
Section: Introductionmentioning
confidence: 99%